2019
DOI: 10.1016/j.neurad.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of the NeVa™ thrombectomy device a novel stent retriever conceived to improve efficacy of organized clot removal

Abstract: The Neva™ device has demonstrated safety and efficacy in a pre-clinical study. Such encouraging, preliminary results have to be compared with those of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Several clinical and experimental studies have evaluated factors related to the failure of MTB17–22 and vessel anatomy has been reported as one of the main factors related to clot removal failure. Zhu et al 13 evaluated the results of patients treated with the Merci retriever device for MCA occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical and experimental studies have evaluated factors related to the failure of MTB17–22 and vessel anatomy has been reported as one of the main factors related to clot removal failure. Zhu et al 13 evaluated the results of patients treated with the Merci retriever device for MCA occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models have endorsed this hypothesis and established NeVa™ to be more efficient than other retrievers. 13,24 Furthermore, both pre-clinical and recent clinical evaluations reported no significant adverse effects caused by the device. Pre-clinical animal studies reported artery wall abrasion due to NeVa™ use to be comparable to other stent retrievers.…”
Section: Discussionmentioning
confidence: 86%
“…Pre-clinical animal studies reported artery wall abrasion due to NeVa™ use to be comparable to other stent retrievers. 12,13,25…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in thrombectomy devices aimed to improve the FPR rate and minimize the incidence of distal and new territory embolization. Device features such as flow control,4 the catheter to the vessel ratio,5 6 the diameter and length of the SR,7 the radial force, and the open architectures of the SRs8 9 have been shown to contribute to the degree of achievement of these procedural endpoints.…”
Section: Introductionmentioning
confidence: 99%